Acute Nonvariceal Gastrointestinal Bleeding: A Comprehensive Review and Approach for an Interventional Radiologist - Mittal, Alok Kumar; Hadidi, Aymen Al; Salam, Basit; Raniga, Sameer Bhimji; Taranikanti, Varna (The Arab Journal of Interventional Radiology, 2023)
Gastrointestinal bleeding (GIB) is one of the most common leading life-threatening conditions requiring prompt diagnosis and rapid endoscopic and interventional radiology (IR) management. Endoscopy is the first line of management for upper GIB, while it has a limited role in lower GIB, especially in acute clinical settings, due to poor bowel preparation. Patients with failed and refractory endoscopic management necessitate emergent computed tomography angiography (CTA) evaluation. CTA is crucial in assessing underlying causes and planning transarterial embolization (TAE). It has been almost three decades since IR gained popularity by virtue of increased technical experience, availability of sophisticated hardware, and evolving techniques. Newer embolization agents and catheters, as well as the established role of CTA, have expanded and enhanced the role of IR in the management of GIB. TAE has been proven to be a safe, rapid, effective, and minimally invasive procedure alternative to surgery when endoscopic management fails to control GIB. We present a comprehensive approach for managing nonvariceal GIB, including CTA protocol, anatomical variants, visceral to visceral collateral pathways, and specific embolization techniques. This article will help readers get an insight into TAE that will help better management of patients with GIB.
Keywords: nonvariceal; gastrointestinal bleeding; embolization; embolic materials